Pengaruh Pemberian Ekstrak Buah Honje Hutan (Etlingera hemisphaerica Blume) terhadap Pemulihan Hiperkolesterolemia dan Hipertrigliseridemia pada Mencit (Mus musculus) - Susanti; Aceng Ruyani; Euis Nursa’adah (Jurnal Biosilampari : Jurnal Biologi, 2024)
This study aimed to test the ethanol extract of honje fruit (Etlingera hemisphaerica) in regulating total cholesterol (CT) and triglyceride (TG) levels in mice (Mus musculus).  This study was a limited clinical trial with trials measuring CT and TG levels before and after treatment. measurement of CT and TG levels using four treatment groups (1 control, 2 doses of E. Hemisphaerica  Fruit Ethanol Extract (EEBE) and 1 dose of simvastatin), and each group was replicated by 5 M. musculus. The pathological condition is carried out with high-fat feeding for 10 days. The extract given consisted of two doses of EEBE, namely (0.26 and 0.39) mg / dL body weight (BB), and a comparison drug dose (simvastatin 0.52 mg / dL BB). Data collection has been carried out before and after EEBE administration for 13 days. Based on the BNT test, the average CT levels of the 4 treatment groups before treatment were 198.6 mg / dL and CT levels after treatment were 196.0 mg / dL, then the average TG levels before treatment were 160.2 mg / dL and after treatment was 158.4 mg / dL. While in treatment group 2 with EEBE dose (0.39 mg / g BB) experienced a decrease in CT levels before treatment namely (225.4 mg / dL) until after treatment namely (201.2 mg / dL) by 10.7% and also experienced a decrease in TG levels from before treatment ie (304.2 mg / dL) to after treatment ie (289.2 mg / dL) by 5%.  Based on the results of the study, it was concluded that giving EEBE to potentially reduce CT and TG levels in M. musculus test animals in the three treatment groups.